2003
DOI: 10.1246/cl.2003.772
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-doped Anatase TiO2 Powders as a Visible-light Sensitive Photocatalyst

Abstract: Carbon-doped TiO2 powders in an anatase phase colored yellow were fabricated by oxidative annealing of TiC. Carbons were located at oxygen sites. The carbon substitution caused the absorbance edge of TiO2 to be shifted to the higher wavelength region. Carbon-doped TiO2 showed photocatalytic activities for the decomposition of IPA to CO2 via acetone under visible light (400–530 nm) irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
511
0
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 919 publications
(541 citation statements)
references
References 13 publications
24
511
0
6
Order By: Relevance
“…Carbon-doping has been reported to enhance the photoactivity of TiO 2 [8,9,25]. This is supported by the observation made earlier about higher dopant content resulting in higher photocurrent density.…”
Section: Photocurrent Density Measurementssupporting
confidence: 63%
“…Carbon-doping has been reported to enhance the photoactivity of TiO 2 [8,9,25]. This is supported by the observation made earlier about higher dopant content resulting in higher photocurrent density.…”
Section: Photocurrent Density Measurementssupporting
confidence: 63%
“…These studies showed that carbon addition to TiO 2 lowered the band gap and make them active under irradiation with visible light. Spray pyrolysis of Ti with carbonaceous precursors (43)(44)(45) and oxidation of TiC (46)(47)(48)(49) can be also applied for preparation of TiO 2 modified by carbon. In the previous studies researches revealed (45) that C doping decreased the energy band gap of TiO 2 from 3.2 to 2.78 eV and created a new energy band located above the valence band with energy of 1.45 eV.…”
Section: Introductionmentioning
confidence: 99%
“…[27] Depending on its source, carbon can be displayed either as a substitutional anion or as an interstitial cation. [28,29] In the former case, Ti-C bond is observed, while in the latter one C-O (carbonate) bond is more likely. [30,31] Nonetheless, Kirsh et al reported that carbon efficiency is not due to a modification of titania lattice, but carbon species, differently from nitrogen, act as sensitizers, injecting electrons from the dopant to the conduction band of titania.…”
Section: Introductionmentioning
confidence: 99%